Javanese Women Hybridity: Postcolonial Study of Nyonya Muluk in Damar Kurung Paintings - Aniendya Christianna (Graduate School of Institut Seni Indonesia Yogyakarta, 2020)
ABSTRACTDamar Kurung is a typical lantern of Gresik, made in the 16th century. In 2017 Damar Kurung was declared an intangible cultural heritage by the Indonesian Ministry of Education and Culture. Masmundari (1904-2005) was a female artist who painted Damar Kurung based on skills learned from her ancestors. Among Masmundari's many paintings, Nyonya Muluk is the most frequently painted. Nyonya Muluk is described as a big woman wearing a dress and wings. Many people say that Nyonya Muluk is a picture of Queen Wilhemina that Masmundari has seen directly. To uncover Nyonya Muluk's identity, it is necessary to explain the image and meaning of this traditional art, the author uses Bahasa Rupa method (Tabrani, 2012), which analyzes the contents of the wimba, cara wimba, tata ungkapan and how to read wimba. Then, analyzed using postcolonial theory, specifically using the concepts of hybridity and mimicry to find out the identity of Nyonya Muluk. Finally, this research is to produce (1) A description of the relationship between the two cultures (East and West/invaders and colonized) which is manifested in the figure of Nyonya Muluk. (2) Nyonya Muluk is a representation of Javanese women's hybridity that illustrates the hopes and dreams of Masmundari (as an East representative) to be similar to the West.Hibriditas Perempuan Jawa: Studi Poskolonial Figur Nyonya Muluk Di Lukisan Damar KurungABSTRAKDamar Kurung adalah lentera khas Gresik, dibuat pada abad ke-16. Pada 2017 Damar Kurung dinyatakan sebagai warisan budaya tak bendawi oleh Kementerian Pendidikan dan Kebudayaan Indonesia. Masmundari (1904-2005) adalah seniman perempuan yang melukis Damar Kurung berdasarkan keterampilan yang diperolehnya secara turun temurun. Di antara banyak lukisan Masmundari, Nyonya Muluk adalah yang paling sering dilukis. Nyonya Muluk digambarkan sebagai perempuan berukuran besar yang mengenakan gaun dan memiliki sepasang sayap. Banyak orang mengatakan bahwa Nyonya Muluk adalah gambaran Ratu Wilhemina yang langsung dilihat Masmundari. Untuk mengungkap identitas Nyonya Muluk, perlu menjelaskan gambar dan makna seni lukis tradisi ini, penulis menggunakan metode Bahasa Rupa (Tabrani, 2012), yang menganalisis isi wimba, cara wimba, tata cara dan cara membaca wimba. Kemudian, dianalisis menggunakan teori postkolonial, khususnya menggunakan konsep hibriditas dan mimikri untuk mengetahui identitas Nyonya Muluk. Akhirnya, penelitian menghasilkan (1) Deskripsi hubungan antara dua budaya (Timur dan Barat/penjajah dan terjajah) yang dimanifestasikan dalam sosok Nyonya Muluk. (2) Nyonya Muluk adalah representasi dari hibriditas perempuan Jawa yang menggambarkan harapan dan impian Masmundari (sebagai perwakilan Timur) untuk menjadi serupa dengan Barat.